2022
DOI: 10.1039/d2py00771a
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-free aziridine-based step-growth polymerization: a facile approach to optically active poly(sulfonamide amine)s and poly(sulfonamide dithiocarbamate)s

Abstract: A highly facile catalyst-free synthetic methodology for optically active polysulfonamide derivatives with controlled linear architecture has been established based on chiral bis(2-substituted N-sulfonyl aziridine)s. Novel poly(sulfonamide amine)s are prepared in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Step-growth polymerization of bis(N-sulfonyl aziridine)s (our previous work 35,36,38 and this work).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Step-growth polymerization of bis(N-sulfonyl aziridine)s (our previous work 35,36,38 and this work).…”
Section: Methodsmentioning
confidence: 97%
“…34 Our group reported the facile synthesis of linear polysulfonamides via step-growth polymerization of bis(N-sulfonyl aziridine) with dinucleophiles, including dicarboxylic acid, diphenol, dithiol, diamine, and bis(dialkyldithiocarbamate)s (Scheme 1). 35,36 Very recently, Rupar reported the polymerization of bis(N-carbonyl aziridine)s with dinucleophiles to form polyamide copolymers. 37 Besides polyaddition, cycloaddition polymerization of bis(N-sulfonyl aziridine) with diisocyanates can produce novel poly(thiazolidin-2-imine)s (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yoon and Zhang independently reported a series of bis(N-sulfonyl aziridine) monomers, which can be polymerized with various dinucleophiles such as dicarboxylic acids, diphenols, dithiols and diamines. [25][26][27][28][29] We recently reported on chain-growth AROP of carbamate activated aziridines 11 and the step-growth polymerization bis(Ncarbonyl aziridine)s with dinucleophiles (Scheme 1d). 30 We found that bis(N-carbonyl aziridine)s rapidly polymerize with a variety of dinucleophiles, including dicarboxylic acids to produced PEAs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yoon and Zhang independently reported a series of bis( N -sulfonyl aziridine) monomers, which can be polymerized with various dinucleophiles such as dicarboxylic acids, diphenols, dithiols and diamines. 25–29…”
Section: Introductionmentioning
confidence: 99%
“…Our work builds on the development of the anionic polymerization of N -sulfonyl aziridines (Scheme b), which are now recognized as valuable monomers to prepare poly­( N -sulfonyl aziridine), poly­(sulfonamide amine), polyimines, thiacyclic polymers, and poly­( N -sulfonyl aziridine) containing copolymers and composites. We have also recently reported the polymerization of a tert -butyloxycarbonyl (BOC)-activated aziridine, demonstrating that non-sulfonyl electron-withdrawing groups can support anionic aziridine polymerizations . The versatility of N -sulfonyl aziridines has expanded with reports that bis­( N -sulfonyl aziridine)­s form polysulfonamides, the sulfonyl analogues of amides, upon reaction with dinucleophiles.…”
Section: Introductionmentioning
confidence: 99%